Woman's Rebellion in Sidney Sheldon's Novel If Tomorrow Comes (1985): A Feminist Perspective - Soraya, Erni Nurhayati; , Dr. Phil. Dewi Candraningrum, M. Ed; , Nur Hidayat, S.Pd (2013)
The study is to reveal how women's rebellion is reflected in If Tomorrow Comes by Sidney Sheldon published in 1985. The objective of the study is to analyze the novel based on structural elements and to analyze women's rebellion based on feminist perspective. The object of the study is a novel If Tomorrow Comes by Sidney Sheldon. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source and the object of study is the novel itself, and the secondary data source is any literature information related to this study. The methods of collecting data are searching through the internet, library reviewing and analyzing based on feminist perspective. Based on the analysis, the researcher draws two conclusions: first, based on the structural analysis of the novel, it has an important role to build up the story so each element cannot be separated from the other. Second, based on the feminist perspective, Sidney Sheldon's novel shows that woman's rebellion gets a lot of injustice treatment and being underestimated by men. That is why she becomes suffered and she revenges, rebels her lives. Sheldon also criticizes the woman's struggle to get the same opportunity using their power. In this novel Sidney Sheldon apparently shows that woman can undergo the oppression condition in her life.